Effect of Pregnancy on the Levels of Blood Cadmium and Lead: analysis of 2006-2011 Nanjing Maternity and Child Health Care Hospital Survey Data. - Kangsheng Liu; Pingqing Gu; Wenjun Chen; Juan Shi; Chuan Shi; Li Xia (Tehran University of Medical Sciences, 2013)
Prenatal lead exposure could not only affect various organ systems of the mother, but also provide a plumbeous environment for the fetus and newborns, and may affect the fetus in a number of detrimental ways. The aim of this study was to adequately determine the interaction between these factors and risky behaviors such as smoking.Data from Nanjing Maternity and Child Health Care Hospital survey during the years of 2006-2011 were used (n = 4400) to evaluate the effections of age, parity, body mass index (BMI), race/ethnicity, pregnancy, iron (Fe) storage status and smoking status on the consumption of the levels of blood cadmium (Cd) and lead (Pb) of females aged 16-35yr old. The blood samples were sent to determine blood lead / cadmium concentration by the Inductively Coupled Plasma Mass Spectrometry (ICP-MS). STATA 12.1 software (www.stata.com) was used to fit regression models for each of the two metals.For both of the two metals, age was positively while BMI was negatively associated with the levels of these metals in blood. Smokers showed statistically significantly higher levels of Cd and Pb (P=0.007), while irrespective of race/ethnicity and Fe storage status as compared to nonsmokers.Novel to this study, pregnancy was found to be associated with significantly lower levels of Cd and Pb, while irrespective of race/ethnicity and Fe storage status as compared to non-pregnant females. It is conceivable that pregnancy could thus accelerate clearance of these metals in the blood.